Angkatan Darat Yang Melakukan Tindak Pidana Asusila Di Muka Umum - Yuda Prihandana; Sherly Adam; Leony Lokollo (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2021)
Introductioan: In criminal cases committed by a military soldier, it must be resolved within the Military Court. Including if an unscrupulous military soldier commits an immoral crime in public.Purposes of the Research:  Analyzing and discussing the application of the elements of criminal acts in Article 281 of the Criminal Code has been fulfilled in immoral crimes committed by soldiers and analyzing and discussing Army soldiers who commit immoral crimes in public can be applied to Article 281 of the Criminal Cod. Methods of the Research:  The method used is normative legal research. The research approach is a statutory approach, a conceptual approach and qa case approach. Sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials is through literature study and then analyzed through a perspective using qualitative methods. Results of the Research: The results showed that the application of the elements of criminal acts in Article 281 of the Criminal Code against TNI AD soldiers who committed immoral crimes in public in Military Decision Number 121-K/PM-III-18/AD/XI/2019, based on legal considerations of military judges that the defendant (TNI AD soldier) was proven guilty and convincingly committed an immoral crime in public, the elements of Article 281 of the Criminal Code have been fulfilled, namely the element of whoever, intentionally and openly violates decency, so that TNI AD soldiers who commit immoral crimes in public are sentenced or be subject to a criminal sanction of 3 (three) months in prison. and stipulates that during the time the defendant is in temporary detention, the total amount of the sentence imposed is deducted. Indonesian Army soldiers who commit immoral criminal acts in public can be applied to Article 281 of the Criminal Code, because in the Military Criminal Code it has not been specifically regulated regarding immoral acts that can be imposed on members of the Army and although the Military Criminal Code is a Lex specialis or specificity of the Criminal Code, it must remain refers to the Criminal Code.